2012
DOI: 10.1161/circulationaha.112.099754
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Microsomal Prostaglandin E 2 Synthase-1 in Bone Marrow–Derived Myeloid Cells Impairs Left Ventricular Function and Increases Mortality After Acute Myocardial Infarction

Abstract: Background-Microsomal prostaglandin E 2 synthase-1 (mPGES-1), encoded by the Ptges gene, catalyzes prostaglandin E 2 biosynthesis and is expressed by leukocytes, cardiac myocytes, and cardiac fibroblasts. Ptges Ϫ/Ϫ mice develop more left ventricle (LV) dilation, worse LV contractile function, and higher LV end-diastolic pressure than Ptges ϩ/ϩ mice after myocardial infarction. In this study, we define the role of mPGES-1 in bone marrow-derived leukocytes in the recovery of LV function after coronary ligation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
(63 reference statements)
0
24
2
Order By: Relevance
“…Because platelet ERK5 is activated by ROS, thrombin, and thromboxane, ERK5 activation in an ischemic environment was explored using a mouse myocardial infarction (MI) model in which these mediators have significant pathologic roles 2830 . As a chronic MI model the left anterior descending (LAD) coronary artery was permanently ligated.…”
Section: Resultsmentioning
confidence: 99%
“…Because platelet ERK5 is activated by ROS, thrombin, and thromboxane, ERK5 activation in an ischemic environment was explored using a mouse myocardial infarction (MI) model in which these mediators have significant pathologic roles 2830 . As a chronic MI model the left anterior descending (LAD) coronary artery was permanently ligated.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the induction of the mPGES-1 protein was mainly produced from inflammatory cells of the heart after myocardial infarction [15]. Thus, by using the bone marrow transplant approach, Degousee's group further demonstrated that inactivation of mPGES-1 in bone marrow-derived leukocytes fully replicated the deleterious remodeling phenotypes and decreased the post-MI survival [70]. Surprisingly, although mPGES-1 was lacking in bone marrow leukocytes, an even higher level of PGE 2 was detected in infarct and viable myocardium.…”
Section: Mpges-1 and Myocardial Remodelingmentioning
confidence: 99%
“…Cardiac PGE 2 generation increases during acute MI17. Despite the expression of multiple PGE 2 receptor subtypes in hearts, selective stimulation of the Ep3 receptor displays cardio-protection against ischaemia/reperfusion injury in different mammalian species35363738.…”
Section: Discussionmentioning
confidence: 99%
“…Disabling PGE 2 generation by mPGHS-1 deletion leads to increased infarct sizes and adverse left ventricular remodelling after MI in mice16. Interestingly, mice with mPGES-1 deletion in bone marrow-derived myeloid cells alone displayssimilar cardiac phenotypes in global mPGES-1-deficient mice as subjected to coronary ligation17, strongly implicating Mos/Mps-derived PGE 2 in wound healing after MI. However, the underlying mechanisms are largely unknown.…”
mentioning
confidence: 99%